2021
DOI: 10.1016/j.asmr.2021.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Age Significantly Affects Response Rate to Outcomes Questionnaires Using Mobile Messaging Software

Abstract: Purpose: To investigate the demographic factors that influence time to respond (TTR), time to completion (TTC), and response rate when using a text messaging-based system and to determine the feasibility and applicability of mobile messaging-based services for collection of patient-reported outcomes among orthopaedic sports medicine patients. Methods: On the day of surgery, patient mobile phone number was collected and the automated mobile messaging service (MOSIO, Seattle, WA) messaged patients for 10``days p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…‡ Contrary to our finding, some studies found older age to be associated with worse response rates. 3,10,15,16,26,34,38 When this occurs, it could distort (i.e., lower) postoperative PROM scores in a population of patients who have undergone RCR due to worse overall outcomes for this population. For example, older patients have higher retear rates.…”
Section: Discussionmentioning
confidence: 99%
“…‡ Contrary to our finding, some studies found older age to be associated with worse response rates. 3,10,15,16,26,34,38 When this occurs, it could distort (i.e., lower) postoperative PROM scores in a population of patients who have undergone RCR due to worse overall outcomes for this population. For example, older patients have higher retear rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, when using collection systems that feature SMS text messaging to send PROMs to patients, sex differences in response rates are no longer present, and younger patients are instead the most responsive age group instead of being the least responsive group. 10,31 With this in mind, the validated 7-item Short-WOSI may lend itself to more easily be incorporated into SMS text messaging systems when compared with the full-length WOSI instrument. Other studies have used automated text messaging to deliver PROM questionnaires with a similar number of items to patient populations ranging from those with anterior cruciate ligament injuries to knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%